Vegetation change in road slopes in the Mediterranean region over 25 years - Enríquez-de-Salamanca, Álvaro (Journal of Environmental Engineering and Landscape Management, 2022)
Revegetation effectiveness requires long-term monitoring. We analysed 50 road slopes 5–8 years and 22–25 years after revegetation. Plant cover and diversity increased over time, with differences between slope types; herbaceous cover increased greatly between revegetation works and 2002 and was similar in 2002 and 2019, while woody cover decreased from revegetation to 2002 but increased greatly between 2002 and 2019. Plant colonisation was more intense on embankments, but could also be achieved on roadcuts (2.4 points on average over a maximum of 5). The presence of sown species decreased over time, but the presence of planted species remained stable. Hydroseeding had poor results in terms of the resulting plant cover, but nevertheless succeeded in slowing erosion at least sufficiently to allow early plant establishment and thus the start of colonisation. The similarity between surrounding vegetation and the slopes was greater in roadcuts. Roads are a gateway for invasive plants. Native species can improve the results, but many are missing from the market. Slopes’ plant cover changed over time; long-term studies are required.